Optimasi Pemilihan Takjil Berbasis Multi-Attribute Decision Making dengan Model Yager - Muhamad Radzi Rathomi; Ritha, Nola; Hayaty, Nurul (JISTech : Journal of Information Systems and Technology, 2025)
The choice of takjil as an iftar dish is frequently decided subjectively, neglecting certain elements that could affect the optimality of the decision. This study employs Multi-Attribute Decision Making (MADM) utilizing the Yager Model to identify the optimal takjil alternative based on established criteria. The five primary criteria employed in this analysis are flavor, cost, nutritional value, accessibility, and feasibility. The calculating method initiates with data standardization, weight allocation, and the implementation of the Yager Model to derive the preference value for each choice. Of the seven evaluated alternatives, the findings demonstrate that Kolak Pisang is the most advantageous option, attaining the maximum minimum value of 0.919. Consequently, this strategy serves as a more rational and objective means of selecting takjil that corresponds with consumer preferences and requirements. The utilization of the Yager Model in alternative contexts offers prospects for additional research in multi-criteria decision-making